Does Family Functioning Matter More Than School Culture? Understanding Deeper Junior High School Student’s Character Strength with Spirituality as mediator - Hetti Sari Ramadhani, S.Psi., M.Si; Jatie K Pudjibudojo; Lena N Panjaitan (Universitas Ahmad Dahlan, 2023)
Previous research has shown that character strength significantly impacts students' future success. This study examines the functioning of family and school culture as antecedents of character strength through spirituality as mediators. The research sample was 1871 junior high school students in Surabaya City consisting of 1010 female students and 861 male students selected by proportional cluster random sampling from five areas of Surabaya City. The research instruments used were the character strength scale of human dimension of Values in Action Inventory for adolescents (VIA-Youth), spirituality scale of Aspects of Spirituality Questionnaire (ASP) Version 2.1., family functioning scale of Family Assessment Device (FAD), and school culture scale of School Climate and School Identification Measure—Student (SCASIM-St). The study was conducted by testing research instruments using confirmatory factor analysis and model testing using Structural Equation Modeling (SEM) analysis. The results showed that the fit, family functioning had a more significant influence than school culture did in shaping student character strength in the human dimension and spirituality model proved to significantly mediate the functioning of family and school culture and the strength of student character on the human dimension. The implications of the study results are expected to accelerate the improvement of student character strength in the humanitarian dimension and become policy recommendations for human resource development that are ready to face various challenges.